2000
DOI: 10.1007/s00585-000-1027-5
|View full text |Cite
|
Sign up to set email alerts
|

Plasma structure within poleward-moving cusp/cleft auroral transients: EISCAT Svalbard radar observations and an explanation in terms of large local time extent of events

Abstract: Abstract. We report high-resolution observations of the southward-IMF cusp/cleft ionosphere made on December 16th 1998 by the EISCAT (European incoherent scatter) Svalbard radar (ESR), and compare them with observations of dayside auroral luminosity, as seen at a wavelength of 630 nm by a meridian scanning photometer at Ny A Ê lesund, and of plasma¯ows, as seen by the CUTLASS (co-operative UK twin location auroral sounding system) Finland HF radar. The optical data reveal a series of poleward-moving transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 53 publications
3
23
0
Order By: Relevance
“…Around the black vertical lines, the electron density showed clear enhancements, which matched well to the events seen propagating poleward in the low‐elevation beam, while the ion temperatures were also enhanced, indicating convection electric field enhancements [e.g., Pitout et al , 2002]. The electron temperature decreased at the time that the patches passed through the field‐aligned beam, consistent with previous observations of high electron density and low electron temperature in the polar cap patches reported by Lockwood et al [2000, 2005a, 2005b] and Moen et al [2004].…”
Section: Observationssupporting
confidence: 87%
See 2 more Smart Citations
“…Around the black vertical lines, the electron density showed clear enhancements, which matched well to the events seen propagating poleward in the low‐elevation beam, while the ion temperatures were also enhanced, indicating convection electric field enhancements [e.g., Pitout et al , 2002]. The electron temperature decreased at the time that the patches passed through the field‐aligned beam, consistent with previous observations of high electron density and low electron temperature in the polar cap patches reported by Lockwood et al [2000, 2005a, 2005b] and Moen et al [2004].…”
Section: Observationssupporting
confidence: 87%
“…The early work of Elphic et al [1990] demonstrated that ionospheric flow bursts measured by European Incoherent Scatter (EISCAT) were associated with FTEs observed by the International Sun‐Earth Explorer (ISEE) and the first magnetically conjugate measurements of an FTE by Equator‐S and of ionospheric flow bursts by SuperDARN were presented by Neudegg et al [1999]. Poleward moving events or poleward moving flow channels, observed by the EISCAT radar, are widely accepted to be associated with bursts in the rate of dayside magnetopause reconnection generating new open flux [e.g., Davis and Lockwood , 1996; Lockwood et al , 1993a, 2000, 2001a, 2001b, 2005a, 2005b; Pitout et al , 2002; Oksavik et al , 2004, 2005; Rinne et al , 2010]. Poleward moving plasma concentration enhancements (sometimes called “polar cap patches”) [ Davies et al , 2002] are frequently observed in the F region of the polar ionosphere during periods of southward interplanetary magnetic field (IMF), and are also thought to be associated with bursty reconnection [e.g., Lockwood and Carlson , 1992; Carlson et al , 2002, 2004].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fast plasma flow can cause a rapid depletion of ionization because of the increased O + + N 2 reaction rate associated with ion‐neutral frictional heating [ Schunk et al , 1975]. Another mechanism is the rapid transport of less dense plasma from other MLTs [e.g., Valladares et al , 1996; Lockwood et al , 2000].…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Observations reported in this paper occurred during a period of extended small northward IMF Bz, with generally larger By and Bx. Opgenoorth et al [2001] have suggested a minor excursion of Bz toward small values between 1305 and 1312 UT which, together with a negative excursion of By, allowed for the occurrence of subsolar (Bz southern type) reconnection in the northern hemisphere prenoon region [ Lockwood et al , 2000].…”
Section: Discussionmentioning
confidence: 99%